Current Practices of Antiseptic Use in Canadian Neonatal Intensive Care Units - McCord, Helen; Fieldhouse, Elise; El-Naggar, Walid (American Journal of Perinatology, 2019)
Objective This article assesses the degree of variability in the current practice of skin antiseptics used in Canadian neonatal intensive care units (NICUs) and different experiences related to each antiseptic used.Methods An anonymous survey was distributed to a clinical representative of each of the 124 Canadian level II and level III NICUs.Results One hundred and two respondents (82.2%), representing all Canadian provinces, completed the survey. Chlorhexidine gluconate with/without alcohol was the antiseptic most used (96%) and the antiseptic with the highest reported adverse effects (68% reported skin burns/breakdown). Other antiseptics used include povidone-iodine (35%) and isopropyl alcohol (22%). Specific guidelines for antiseptic use were available in only 50% of the units with many NICUs lacking gestational and/or chronological age restrictions. Only 23% of responders believed that there was awareness among health care providers of the adverse effects of antiseptics used. Less than half (43%) were completely satisfied with the antiseptics used in their units.Conclusion Chlorhexidine gluconate is the most commonly used antiseptic in Canadian NICUs. The high number of associated adverse effects and the lack of guidelines regulating antiseptic use are of concern. Large clinical trials are urgently needed to guide practice and improve the safety of antiseptics.
Keywords: anti-infective agents; newborn/premature infants; skin antiseptics